2016
DOI: 10.1186/s12885-016-2513-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcome of Ganglioneuroma and Ganglioneuroblastoma intermixed

Abstract: BackgroundGanglioneuroma (GN) and ganglioneuroblastoma intermixed (GNBI) are mature variants of neuroblastic tumors (NT). It is still discussed whether incomplete resection of GN/GNBI impairs the outcome of patients.MethodsClinical characteristics and outcome of localized GN/GNBI were retrospectively compared to localized neuroblastoma (NB) and ganglioneuroblastoma-nodular (GNBN) registered in the German neuroblastoma trials between 2000 and 2010.ResultsOf 808 consecutive localized NT, 162 (20 %) were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
130
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 30 publications
(43 reference statements)
10
130
1
2
Order By: Relevance
“…In addition, DeCarolis et al. reported that only 5 of 55 patients with imaging‐detectable residual GN and GNB‐I tumors on GPOH NB97 and NB 2004 demonstrated evidence of local progression and all 5 went on to have SD following repeat partial resection (N = 3), biopsy (N = 1), or chemotherapy (N = 1) . Importantly, this study also supported a previous report demonstrating no role for cytotoxic therapy for GN and GNB‐I .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, DeCarolis et al. reported that only 5 of 55 patients with imaging‐detectable residual GN and GNB‐I tumors on GPOH NB97 and NB 2004 demonstrated evidence of local progression and all 5 went on to have SD following repeat partial resection (N = 3), biopsy (N = 1), or chemotherapy (N = 1) . Importantly, this study also supported a previous report demonstrating no role for cytotoxic therapy for GN and GNB‐I .…”
Section: Discussionsupporting
confidence: 89%
“…Several recent case series of patients with GN have advocated consideration of nonradical surgeries and/or observation approaches rather than complete surgical resection . To our knowledge, this report is the first to describe the natural history and growth over time for unresected GN and GNB‐I tumors.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations